Quality Improvement As A Strategy to Build Pesantren's Brand Credibility - Hasan Baharun; Enas Enas; Rafika Laura Noviana (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this research is to understand quality improvement as a strategy to build brand credibility in one of the pesantren in the Probolinggo Regency. This research uses a qualitative case study approach. Interviews, observations, and documentation are used to obtain data in the field. The informants in this study consisted of pesantren leaders, administrators, teachers, students, and alumni. Milles and Huberman’s design is used in the data analysis, including collecting data, reducing it, presenting it, and drawing conclusions. The results showed that the quality improvement carried out by one of the pesantren in Probolinggo Regency in building its brand credibility was through; the benefit of technology integration, harmonized relationship with alumni, cashless, service quality, and benchmarking. This study has implications for the importance of the credibility of pesantren in increasing bargaining power and public trust so that pesantren are no longer used as educational institutions that are underestimated.